(untitled) (Vietnam Journal of Community Medicine, 2025)
Objects: To describe the current level the knowledge of prevention and management of anaphylaxis and some related factors among final-year students at the Thanh Hoa Campus of Hanoi Medical University. Methods: A cross-sectional study of 180 final-year students at the Thanh Hoa Campus of Hanoi Medical University in the 2024–2025 academic year, using a self-administered questionnaire. Results: A significant proportion of students (67.2%) demonstrated a below-average level of knowledge regarding anaphylaxis prevention and management, while only 32.8% achieved a good or excellent level. Factors such as gender and prior experience witnessing an anaphylactic event were statistically associated with knowledge levels (p < 0.05). Conclusion: The knowledge of final-year students at the Thanh Hoa Campus of Hanoi Medical University regarding the prevention and management of anaphylaxis is not high. Gender and experience in witnessing anaphylaxis influence students’ knowledge of anaphylaxis prevention and management.